Channel size effect on drift-flux parameters for adiabatic and boiling two-phase flows. (April 2022) - Hibiki, Takashi; Ju, Peng; Rassame, Somboon; Miwa, Shuichiro; Shen, Xiuzhong; Ozaki, Tetsuhiro
Highlights: The channel size effect on drift-flux parameters is detailed. Critical size such as 30 times Laplace length does not apply to non-circular channels. The bundle distribution parameter depends on bundle casing geometry and rod array. The channel size effect is more pronounced at low pressure and low flow conditions. The channel size has less impact for beyond-bubbly flows. Abstract: Gas-liquid two-phase flows are utilized in various heat and mass transfer processes that appear in numerous industrial apparatus. Typical examples are chemical reactors, heat exchangers, nuclear reactors, deaerators, condensers, etc. The numerical simulation of gas-liquid two-phase flows, which is crucial for efficient, safe, and optimized apparatus design, requires an accurate model developed based on the physics of the two-phase fluid dynamics. The two-fluid model is considered the most accurate two-phase conservation equations used in computer simulation codes to predict the thermal-hydraulic behavior of two-phase flows. The drift-flux parameters, such as the distribution parameter and drift velocity in the drift-flux model, are utilized in formulating the interfacial drag force in the two-fluid model-based simulation codes. The drift-flux model is an insightful model considering the difference between gas and liquid velocities. The effect of phase and velocity distributions on the void fraction is considered through the two drift-flux parameters. The distribution parameter and drift velocity are critical parameters in the two-phase flow formulation through the two-fluid model, which are the backbone of thermal-hydraulic analysis codes. The constitutive equations for the distribution parameter and drift velocity developed for medium-size channels reach a mature level but do not apply to industrial-size channels or large-size channels. The complicated two-phase flow dynamics in large-size channels affect the distribution parameter and drift velocity significantly. The distribution parameter in a large-size channel increases at low pressure and low liquid flow conditions due to induced secondary flow in the large-size channel. The drift velocity also increases due to cap bubbles formed by the surface instability of large bubbles. Multi-dimensional two-phase flow dynamics observed in large-size channels complicate the distribution parameter and drift velocity modeling. Thus, the drift-flux modeling in large-size channels is a much more subtle task than that in medium-size channels. This fact has driven the research to establish the drift-flux type correlations by modeling the distribution parameter and drift velocity in large-size channels. The current paper aims to provide state-of-the-art knowledge of the current status of the recent development of the drift-flux type correlations in large-size channels. The discussed items cover the formulation of the one-dimensional drift-flux model, typical drift-flux correlations developed for medium-size channels, distribution parameters for subcooled and saturated boiling flows, unique two-phase flow dynamics in large-size channels, critical size at the boundary between medium and large-size channels, and existing drift-flux correlations for large-size channels. The flow channel geometries discussed in the current paper are circular, annulus, rectangular, square, vertical rod bundle, and horizontal tube bundle. The future research direction is also discussed.